A Multimodal Discursive Analysis of the Communicative Elements of Sexism in Facebook Picture Uploads - Mahmud , ’Yemi; Idegbekwe, Destiny (International Journal of Language and Literary Studies, 2020)
A good number of studies in the past have examined the language of sexism from the feminist perspectives, gender segregation and degradation, among others, using semiotics resources, discourse analysis, multimodal discourse, among other theories. This study looks at the linguistic and non-linguistic language features of sexist language as choices available to language users on the Facebook social media platform. Using the multimodal theory as the framework, the study examines 10 randomly selected Facebook posts with texted pictures and comments posted by Nigerians with elements of sexism. The study also engaged the descriptive research design to examine the ‘textedpictures’ used as sampled data. These sampled data were given in-depth analysis to reveal their usually hidden and laughed-about sexist messages. The analysis of data was considered by determining the existence of sexist communication on Facebook platform, examining the meaning making elements in sexist languages posts. This is precipitated on the discovery that less attention is paid on the signification of the communicative elements deployed to convey sexism on the Facebook platform. From the analysis, the study finds out that Facebook users engage linguistic and non-linguistic elements symbolising sexist language on Facebook postings; that the posts on Facebook rely predominantly on both written texts and pictures, combined to make the tagging or stereotyping concrete; that the sexist posts on Facebook platforms rely heavily on hasty or intentional generalisation in order to demean the sex they chose to target through texts, pictures and the combination of texts and pictures.